A Need of HOTS-Based English Book for Ninth Grade Students - Kristian, Ananda Kevin (STKIP AGAMA HINDU SINGARAJA, 2022)
A learning process is supported by essential aspects such as syllabus, learning material, lesson plan, and textbook. The educator lately found that the handbook used still not fulfilled some of the criteria of a good quality handbook. Therefore, the research aims to develop the English Handbook for the second semester of ninth-grade students in junior high school. The current research is D&D research. The instrument used were an observation sheet, interview guide, syllabus, and expert judgment. The participants were the English teacher of SMP Negeri 3 Singaraja. The data gathered qwere analyzed qualitatively and quantitively. The need analysis results found that the teacher and students did not understand the whole concept of HOTs. The supporting media also still not be variated as required to implement the HOTS in the learning process. Therefore, the results implied supporting the learning process with a good learning activity, media, and content based on HOTs.